Dimensional analysis under Pythagorean fuzzy set with Hesitant linguists term entropy information - Villa Silva, A. J.; Pérez Domínguez, Luis; Martínez Gómez, E.; Romero López, R.; Valles Rosales, D. J. (2021)
Currently Pythagorean Fuzzy Set (PFS), is an important tool for handling fuzziness and vagueness, therefore, is able to make decision makers simple to provide their assessments. In other hand Dimensional Analysis (DA) is a technique able to criteria capturing the interrelationship. The aim of this paper is to present the DA with PFS to overcome limitations to handle qualitative (intangible) as well as the interactions between arguments, and entropy measure for linguistic term sets (HFLTSs) is applied to overcome criteria weights problems.